Biodegradation of Petroleum Hydrocarbons by Microbial Consortia - Mohamad Ghazali, Farinazleen (2004)
This investigation consisted of a series of studies designed with the primary objective of constructing microbial formulations or consortia that could effectively bioremediate hydrocarbon pollutions by way of their metabolic capabilities. This objective was achieved first by studying 46 bacterial strains that were initially isolated from Malaysian soils and waters that were polluted with hydrocarbons. The screenings on varying concentrations of crude oil resulted in the identification of potential isolates with differing abilities to grow on crude oil or its individual hydrocarbon components. Six bacterial isolates were finally chosen for further investigation and for the construction of bacterial formulations. These isolates consisted of two strains of Pseudomonas sp., three strains of Bacillus sp., and one strain of Micrococcus sp. The Pseudomonas sp. and Micrococcus sp. strains were seen to be able to tolerate and grow in high concentrations (up to 50% v/v) of crude oil and were able to utilize compounds such as aliphatic and monoaromatic hydrocarbons as well as alcohols as substrates.The second section of this study involved the construction of different formulations made up of the six isolates identified in the earlier screening section. The formulations of bacterial consortia consisted of between two and six of the abovementioned strains. Formulations made up of Pseudomonas aeruginosa and Bacillus sp. strains resulted in the highest extent of bioremediation. Between 39.74 and 61.09% of the n-alkanes C10 to C28 was degraded after 30 days of incubation with the bacterial mixture consisting of the two P. aeruginosa sp. and one Bacillus sp. strains. Following the construction of the hydrocarbon-degrading microbial consortia, bioremediation studies were performed which were to make up the third section of this investigation. The growth patterns and degradation of aliphatic components of crude oil were studied in differing concentrations of crude oil and media salinity. Consortium 1, which consisted of P. aeruginosa S4.1, P. aeruginosa S5 and Bacillus sp. S3.2, was more efficient at biodegrading crude oil compared to Consortium 2, which comprised of P. aeruginosa S4.1, P. aeruginosa S5, Bacillus sp. S3.2, Bacillus sp. O63, Bacillus sp. 113i and Micrococcus sp. S. Further bioremediation studies were conducted using Consortium 1. The effects of incubation temperature, agitation rates, media pH, oil-medium interface area, bacterial adaptation, inoculum size, fertilizer addition and surfactant addition were investigated in liquid media. Bioremediation of crude oil by Consortium 1 was most extensive when artificial seawater with pH 7 was used as the culture medium. The addition of 0.1% of Triton X-100, a synthetic surfactant, into the culture medium improved bioremediation. Prior exposure to crude oil of the inoculum also enhanced bioremediation extent and rates. The starting inoculum size of 5% resulted in the highest biodegradation of crude oil. An increased oil-medium interface area also resulted in enhanced bioremediation. The incubation conditions which lead to higher biodegradation extent were at 37ºC and shaken on horizontal shaker at 100 rpm. When conducted under all the optimised parameters described above, Consortium 1 was seen to remove between 55.80 and 70.56% of n-alkanes following a 60-day bioremediation process. In the fourth section of this investigation, the bacterial cells of Consortium 1 were immobilized using calcium alginate to study the possibility of reusing hydrocarbondegrading bacteria in bioremediation processes. The entrapment of the bacterial cells did not impair the biodegradation activity of Consortium 1. The calcium alginate-entrapped cells could also be used repeatedly without loss of biodegradation capacity for up to 5 times or a total of 150 days of use. The fifth and final section of this investigation involved the application of the bacterial consortia onto polluted soil samples in a lab-scale pilot study. Consortia 1 and 2 were tested using beach sand polluted by crude oil and soil polluted by a diesel spill. In contrast to the observations made in liquid media where Consortium 1 was most effective, Consortium 2 was seen to be more effective at removing hydrocarbon contamination in the polluted beach sand and soil. In the beach sand, between 21.01 and 80.19% of alkanes remained after 30 days with Consortium 1 whilst between 15.30 and 27.11% of these compounds remained when Consortium 2 was used. Repeated application of Consortium 2 onto the beach sand resulted in accelerated degradation of crude oil. In the engine-oil polluted soil, it was seen that the addition of Consortium 2 resulted in a rapid removal of hydrocarbons where the aliphatic compounds had fallen to undetectable levels within 30 days.Overall, this investigation had achieved its primary objective of designing microbial formulations or consortia that could be employed in the bioremediation of petroleum hydrocarbon pollutions.